Research on the reverse analyses and monitoring data of Mirai malware botnet - Ya-liang CHEN; Qin-yun DAI; Hai-yan WU; Zheng WEI (网络与信息安全学报)
In recent years,with the rapid development of Internet of things(IoT),malwares have come into Internet of things,and botnet is the typical one.Malwares spreading through IoT vulnerable devices have emerged.The overall structure of Mirai botnet and the function of its components were introduced,such as bots and C＆amp;C server.The monitoring data obtained through active and passive way were analyzed.Based on that,the discovery methods and response modes on such kind of botnet malwares were discussed.